PERIPHRASTIC CONSTRUCTIONS WITH THE VERB IMET’ (TO HAVE) AND THE PASSIVE PARTICIPLE IN PYOTR TOLSTOY’S TRANSLATION OF THE HISTORY OF THE PRESENT STATE OF THE OTTOMAN EMPIRE - Tatiana V. Pentkovskaia (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The article examines the periphrastic constructions, which consist of the verb imet’ (to have) in the form of the present or past tense and the passive participle with the suffix -n- in The History of the Present State of the Ottoman Empire translated by P.A. Tolstoy in the early 18th century. They are noted to appear in certain cases instead of the forms of passato prossimo and trapassato prossimo of the Italian version of this text. First of all, they are used in a meta-text function when referring to the above mentioned or to someone’s words. Such verbal periphrases occur when there is a direct complement in the sentence. The participle in this construction is most often coordinated with the direct object, but in some examples, it can take the form of the neuter singular. This kind of the construction has a typological similarity with the second, or possessive, perfect in a number of Slavic languages (Czech, Kashubian, Macedonian). But unlike the possessive perfect proper, participial forms in such constructions in the translation of The History are formed only from Perfective or Imperfective of transitive verbs. Their use remains characteristic of a specific text, and it is not a part of the grammatical system of the language itself. However, the presence of different models of participle coordination in them indirectly reflects the process of grammaticalization of the passive participle form of the past tense in the Old Russian language.